MONITORING SYSTEM AND PERFORMANCE MEASUREMENT USING WEBSITE-BASED BALANCED SCORECARD METHOD - Suhendra Robby; Nurul Mutiah; Ibnur Russi (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract : Directorate General of State Assets West Kalimantan Regional Office each year has a work program provided by the central DJKN that must be completed, The work program is carried out with the target set by the central DJKN. DJKN has a standard method in measuring each work plan program, namely using the Balanced Scorecard method, But in its application there are still many processes in measuring and monitoring plans that are done manually so that business processes are carried out for a long time and are ineffective and without an information system, the monitoring process cannot be done in real time anywhere and anytime so that some work plans are late accordingly. with targets that will directly affect performance. This study aims to cut the manual business process by using a website-based performance monitoring and measurement system so that it is hoped that the performance monitoring process can be carried out optimally in real time and easily. The results of this research are in the form of a website-based performance monitoring and measurement system that has been tested for system functionalities and system interfaces by obtaining results according to each functional system and system interface available and testing for users at the Directorate General of State Assets West Kalimantan Regional Office obtaining a percentage of 88.55 % .. Keywords : Balanced Scorecard ; DJKN ; Monitoring ; Performance Measurement Abstract : Directorate General State Assets (DGST ) West Kalimantan Regional Office every year year have a given work program by the central DJKN which must completed , work program implemented with the target that has been set by the central DJKN . DJKN has standard method in measure every program plan work that is use the Balanced Scorecard method, but in implementation still many processes in measure and monitoring plan work done manually so that the business processes that are run eat long time and no effective as well as without existence system information make the monitoring process not can done by realtime everywhere and any time so that make a number of plan work late no in accordance with a target that direct will influence performance . Study this aim cut those manual business processes with use monitoring system and measurement performance web -based so that expected performance monitoring process could done by maximum with easy and realtime , Results study this in the form of monitoring system and measurement performance based on a website that has been tested functional system and interface system  with get results in accordance will every functional system and interface existing system _ and testing to users at the West Kalimantan Regional Office DJKN get results percentage 88.55%. Keywords: Balanced Scorecard ; DJKN ; Monitoring ; Performance Measurement